Anticoagulant rodenticide toxicity in six dogs presenting for ocular disease. (19th March 2015) - Griggs, Angela N.; Allbaugh, Rachel A.; Tofflemire, Kyle L.; Ben‐Shlomo, Gil; Whitley, David; Paulsen, Michael E.
Abstract: Objective: To describe cases of suspected anticoagulant rodenticide toxicity manifesting with predominantly ocular signs. Materials and methods: Six canine cases that presented to veterinary referral hospitals for ocular abnormalities and were diagnosed with suspected or confirmed anticoagulant rodenticide ingestion were reviewed for commonalities in presentation and outcome. Results: Five dogs had unilateral ocular signs and one dog had bilateral manifestations. Signs included subconjunctival hemorrhage, exophthalmos, and commonly orbital pain without other significant physical examination findings. Prothrombin time was measured in 5 of 6 dogs and was prolonged in all. Partial thromboplastin time was measured in 4 of 6 dogs and was prolonged in all. Complete blood cell count and serum chemistry profiles demonstrated mild, if any, abnormalities. Five dogs had known anticoagulant rodenticide exposure, and rodenticide ingestion was suspected in 1 additional case based on clinical signs, clinical pathologic abnormalities, and response to treatment. Five of 6 cases were hospitalized overnight for plasma transfusions along with oral or injectable vitamin K1, and all dogs were treated with oral vitamin K1 for 30 days. All dogs experienced complete resolution of clinical signs within 6 weeks of initiating treatment. Conclusions: Anticoagulant rodenticide toxicity can present with predominantly ocular manifestations. Rodenticide ingestion should be considered in dogs with unilateral or bilateral subconjunctival hemorrhage, exophthalmos, and orbital pain.